Atherosclerotic Plaque Characterization Methods Based on Coronary Imaging. - Athanasiou, Lambros S. (Elsevier Science, 2017)
Atherosclerotic Plaque Characterization Methods Based on Coronary Imaging provides a complete review of computer methods for atherosclerotic plaque reconstruction and characterization. The authors, with their expertise from biomedical engineering, computer science, and cardiology, offer a holistic view. The focus of the book is on the presentation of major imaging techniques, including their limitations. It includes details on the mechanical characterization and properties of plaques and appropriate constitutive models to describe the mechanical behavior of plaques. The authors explore the challenges of using multiple coronary imaging technologies, and provide the pros and cons of invasive vs. non-invasive techniques. Methods for plaque characterization and 3D reconstruction of coronary arteries using IVUS, OCT, and CT images are described. This book will help readers study new trends in image processing analysis and plaque characterization, implement automated plaque characterization methodologies, understand coronary imaging drawbacks, and comprehend 3 dimensional coronary artery and plaque reconstruction methods.